High School Teacher’s Opinions and Problems Faced about Using Smart Board in Classroom: Famagusta District Sample - Batu, Yaprak (Eastern Mediterranean University EMU - Doğu Akdeniz Üniversitesi (DAÜ), 2016)
The development of technology has gained meaningful impact and has influenced the educational standard in this era of globalization. This dissertation aims at reviewing the perception of high school teachers, on the use of smart board in schools located in Famagusta (TRNC). A detailed investigation was done on why smart boards are being used as well as major problems faced in the period of usage. Also, the study aims at using the developed research questions to find answers of the problems related to the usage of smart board in the classroom by teachers. As a quantitative research work, one hundred and twenty eight (128) teachers from four selected secondary schools in Famagusta District in TRNC took part in the research. They include both male and female with different educational qualifications. Also variables such as age, profession, experience, weekly usage time of smart board, material design, coursetaken and certificate are major variables employed in the study. Descriptive technique was used in analyzing the general opinions of the teachers while Analysis of Variance (ANOVA) employed in calculating whether opinions deferred due to gender, age, experience or profession. Also, T-test is used in considering the significance between variables. Hence, the result found that age and profession didn’t affect their opinions but the level of experience influenced teacher’s perceptions. Furthermore, the result shows that teachers opinion towards smart-boards differ but not due to their age or profession. Keywords: Smart boards, Interactive Learning, Active learning.

ÖZ: Teknolojinin gelişmesi küreselleşme çağında eğitim standardını anlamlı olarak etkilemiştir. Akıllı tahtaların öğrencilerin kalıcı ve pratik öğrenmesindeki etkisini kanıtlayan birçok araştırma vardır. Bu çalışmanın amacı Kuzey Kıbrıs Türk Cumhuriyetinde bulunan Gazimağusa bölgesindeki lise öğretmenlerinin sınıf içerisinde akıllı tahta kullanımı konusundaki algı ve görüşlerini gözlemlemektir. Akıllı tahtanın kullanılma sebepleri ve kullanımı sırasında yaşanan başlıca problemler detaylı araştırmayla elde edilmiştir. Ayrıca, bu çalışmada öğretmenler tarafından sınıfta akıllı tahta kullanımı kullanımı ile ilgili sorunların cevabını bulmak ve derinlemesine incelemek için araştırma soruları kullanılmıştır. Yapılan nicel çalışmada, Gazimağusa bölgesinden kadın, erkek ve farklı eğitim alanlarından olmak üzere 128 (yüzyirmisekiz) lise öğretmeni yer almıştır. Ayrıca yaş, meslek, deneyim, sertifika, kullanım süresi, materyal tasarım gibi değişkenler de araştırmada ölçek olarak kullanılmıştır. Öğretmenlerin genel düşüncelerini analiz etmek için tanımlayıcı (ANOVA) varyans tekniği kullanılmıştır.Değişkenler arasındaki anlamlı farklılıkları bulmak için ise T-test kullanılmıştır. Bunun sonucunda yaş ve eğitim alanının genel düşünceler üzerinde fazla etkisi olmadığı fakat deneyimin öğretmen düşünceleri üzerinde anlamlı etkisi olduğu saptanmıştır. Anahtar Kelimeler: Akıllı Tahta, İnteraktif Öğrenme, Aktif Öğrenme.
Master of Science in Information and Communication Technologies in Education. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Education, Dept. of Information and Communication Technologies in Education, 2016. Supervisor: Assoc. Prof. Dr. Ersun İşçioğlu.
Keywords: Information and Communication Technologies in Education; Information and Communication Technologies in Education-Higher Education-Famagusta (Cyprus, North); Information Communication Technologies; Educational technology-Information technology; Educational Technology-E-Learning; Whiteboards (Smart Boards); Classroom management-Education-Computer network resources-Educational Tools; Teaching-Computer Network Resources; Smart boards; Interactive Learning; Active learning